Foraging Preference of Giant Honeybee, Apis dorsata F., to Selected Horticultural Crops - Neupane, KR; Dhakal, DD; Thapa, RB; Gautam, DM (Journal of the Institute of Agriculture and Animal Science, 2006)
Foraging preference of giant honeybee, Apis dorsata Fab. to selected horticultural crops, litchi, Litchi chinensis Sonner, lemon, Citrus limon (Lin.) Burm. f., bottlebrush, Callistemon citrinus (Curtis) Skeels, cucumber, Cucumis sativus Lin., radish, Raphanus sativus Lin., and summer squash, Cucurbita pepo L., was studied during their blooming time at IAAS, Rampur, Chitwan, Nepal, 2001. The flowering of all six species of experimental plants started in the first week of March and lasted for two months with a peak flowering from 15 March to 5 April. Foraging preference of bees at 7.30, and 11.00 am and 3.00 pm and 5.30 pm during early, mid and late periods of flowering was assessed. Honeybees foraging at different times of day during early, mid and late flowering periods differed significantly. The highest mean number (8.04/min/m2) of A. dorsata workers was recorded on bottle brush flowers at 7.30 am during early flowering period followed by litchi, summer squash and the lowest (0.25/min/m2) on citrus at 5.30 pm during late flowering period. The bees never visited to the flowers of radish and cucumber. Pollen was preferentially collected from bottlebrush, summer squash and citrus in the morning and nectar from litchi and bottlebrush flowers throughout the day. Pollen foragers spent less time (2.9±1 sec/flower) and visited more flowers (17.9±6/min) when bees collected both pollen and nectar from the same plant. The number of outgoing and incoming foragers were the highest (59.0±14, 44.0±15/min/colony) at 7.30 am during mid flowering period and the lowest (17.6±7, 17.0±2/min/colony) at 5.30 pm during late flowering period, respectively. Key words: Foraging preference, Apis dorsata, horticultural crops J. Inst. Agric. Anim. Sci. 27:87-92 (2006)